The effect of annealing on the energy gap of Polyimide (PI) and Polyethylene terephthalate (PET) Polymers - Abdullah, A.; Jaffer , H.; AL-Shamri, Z. (Iraqi Journal of Science, 2025)
The effect of annealing on the energy gap of PET and Pl has been investigated. The annealing temperature were set at 175, 150, 200 and 2:4101 °C which are less than the Tm of both polymers The energy gap are decreasing for PET and Pl at different temperatures, the experimental results showed that the thermal energy and oxidation are the major factors responsible for the change in the energy gap of PET and PL.